Effect of Spraying With Foliar Fertilizer of a Mixture of Seaweed Extract and Amino Acids on the Growth and Yield of Eggplant (Solanum Melongena L.) - Obaid , Faris Ibrahim; Hashim , Mahmood Shakir (American Journal of Botany and Bioengineering, 2025)
The research was performed at the Agricultural Research Station in the University of Basra, using complete randomised plot. This was factorial experiment where the cultivar singled out and two cultivars: Barcelona and Jawahar were treated and the foliar spraying which was treated by a solution of amino acid and seaweed extract. In the investigated parameters, spraying with the combination of 2 mg L^-1 was found to be better than the Barcelona cultivar. In all aspects, the Barcelona cultivar overlap was found under the spraying of the mixture at a dose of 2 mg L⁻¹ under all of the investigated conditions.